Ankrd6 is a mammalian functional homolog of Drosophila planar cell polarity gene diego and regulates coordinated cellular orientation in the mouse inner ear. - Jones, C.; Qian, D.; Kim, S.M.; Li, S.; Ren, D.; Knapp, L.; Sprinzak, D.; Avraham, K.B.; Matsuzaki, F.; Chi, F.; Chen, P. (Developmental Biology, 2014)
The coordinated polarization of neighboring cells within the plane of the tissue, known as planar cell polarity (PCP), is a recurring theme in biology. It is required for numerous developmental processes for the form and function of many tissues and organs across species. The genetic pathway regulating PCP was first discovered in Drosophila, and an analogous but distinct pathway is emerging in vertebrates. It consists of membrane protein complexes known as core PCP proteins that are conserved across species. Here we report that the over-expression of the murine Ankrd6 (mAnkrd6) gene that shares homology with Drosophila core PCP gene diego causes a typical PCP phenotype in Drosophila, and mAnkrd6 can rescue the loss of function of diego in Drosophila. In mice, mAnkrd6 protein is asymmetrically localized in cells of the inner ear sensory organs, characteristic of components of conserved core PCP complexes. The loss of mAnkrd6 causes PCP defects in the inner ear sensory organs. Moreover, canonical Wnt signaling is significantly increased in mouse embryonic fibroblasts from mAnkrd6 knockout mice in comparison to wild type controls. Together, these results indicated that mAnkrd6 is a functional homolog of the Drosophila diego gene for mammalian PCP regulation and act to suppress canonical Wnt signaling.